The effect of boron-pack refreshment on the boriding of mild steel by the spark plasma sintering (SPS) process - Chen, X. J. (2012)
Mild steel samples were borided with and without boron pack refreshment using the spark plasma sintering (SPS) process. Results show that the borided samples with boron pack refreshment developed a thicker boride layer compared to that without boron pack refreshment for the same boriding duration. When boriding duration is t < 120 min, the boriding growth in the samples borided with boron pack refreshment followed a parabolic growth pattern. In contrast, the boride growth in samples processed without boron-pack refreshment deviates from parabolic at t = 60 min. Computer simulation shows that the boron concentration change in the boriding media during the boriding process is an important factor affecting the composition and final thickness of the boride layer.